E-Participation Success Factors: A Systematic Literature Review - Syam, Elgamar; Abd Wahab, Alawiyah; Husin, Abdullah (Science Publications, 2024)
E-participation which has emerged from the development of electronic government, is a very interesting phenomenon to study today. However, when e-participation was first introduced, various problems arose, such as the reluctance of citizens to use e-participation as a system that was considered suitable to carry out the process of public participation in government. This problem encourages many researchers to find answers and solutions to any problem that arises. This study aims to conduct a systematic review of the diversity of research results related to the key factors for the success of e-participation based on the theoretical basis built by previous researchers. The systematic review was conducted using the Scopus database and the Web of Science (WoS), which are known to have numerous literature sources, especially related to studies on e-participation. In this study, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was used as a method to collect, evaluate, and synthesize related literature. Based on the results of the systematic reviews and analyses conducted, nine of the most relevant studies were identified. Of the nine studies, six theories were found that are commonly used by researchers, namely TAM, D&M IS success model, TPB, SCT, UTAUT, and TOE. In addition, four factors were found to have the strongest influence on e-participation success, namely behavioral factors, perceived ease of use, perceived benefits, and environment. Deepening these theories and factors will provide valuable knowledge and a solid foundation for researchers and stakeholders in the design and implementation of e-participation systems in the future